Pengaruh Free Cash Flow, Struktur Kepemilikan Dan Leverage Tehadap Kebijakan Deviden Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2020-2022 - Evangelista, Maria Ofrida (Jurnal Akuntansi Manajerial, 2024)
This research aims to determine the influence of free cash flow, ownership structure and leverage on dividend policy in manufacturing companies in the consumer goods industry sector listed on the Indonesian Stock Exchange in 2020-2022. Free cash flow is proxied by FCF(X1), ownership structure is proxied by KI(X2), Leverage is proxied by the debt to equity ratio DER(X3), dividend policy is proxied by the dividend payout ratio DPR (Y). The type of research used is quantitative research, the sample used was 49 companies from the population of manufacturing companies in the consumer goods industry sector in 2020-2022. The research results show that; (1) The results of data processing show that free cash flow does not have a significant effect on dividend policy. (2) The results of data processing show that ownership structure does not have a significant effect on dividend policy. (3) The results of the data show that leverage has a positive and significant effect on dividend policy.